Chelidonine Induces Caspase-Dependent and Caspase-Independent Cell Death through G2/M Arrest in the T98G Human Glioblastoma Cell Line. (26th May 2019) - Lee, Yeon-Kyeong; Lee, Ki Won; Kim, Minju; Lee, Yerin; Yoo, Jiyun; Hwangbo, Cheol; Park, Ki Hun; Kim, Kwang Dong
Abstract : Chelidonium majus L. (family Papaveraceae), commonly known as greater celandine or tetterwort, has been reported to have antibacterial and anticancer effects and chelidonine is known as a functional metabolite extracted from C. majus . In this study, we observed the cytotoxicity of the alkaloid, chelidonine, and investigated its functional mechanism in T98G glioblastoma cell line. Chelidonine induced apoptosis in a dose-dependent manner, which was accompanied by decreased antiapoptotic protein Mcl-1. Caspase-3 and -9 were activated by treatment with chelidonine, but chelidonine-mediated apoptosis was only partially inhibited by a pan-caspase inhibitor. Chelidonine also induced the translocation of AIF into the nucleus; therefore, it is likely that chelidonine induces T98G cell death through both caspase-dependent and caspase-independent apoptosis pathways. Chelidonine also inducedG 2 / M arrest by inducing multipolar spindle assembly, which might also lead to cell death through inhibiting mitosis. Active CDK1, one of factors contributing to the prolongation ofG 2 / M phase, induced Mcl-1 degradation increasing mitochondrial instability, which is also an inducer of apoptosis in chelidonine-treated T98G cells. Taken together, these findings indicate that chelidonine induces apoptosis throughG 2 / M arrest and Mcl-1 degradation, implying that it may represent a compound for anticancer chemotherapy.